ISOLASI DAN KARAKTERISASI LIPASE DARI KECAMBAH BIJI ALPUKAT (Persea americana Mill) - Sya'bani, Nurillah; Astuti, Winni; Pratiwi, Djihan Ryn (Jurusan Kimia FMIPA UNMUL, 2017)
Isolation and determination of optimum lipase conditions from Avocado seeds germination (Persea americana Mill) have been done. The purpose of this study is to determine the optimum working conditions and lipase specific activity of avocado seeds germination. Lipase was isolated using homogenization and centrifugation techniques. The crude extract of the enzyme containing the lipase produced from avocado seeds germination was used for the determination of total protein concentration and tested its activity on the pH conditions, temperature, and optimum substrate concentration with different with various variations. Determination of total concentration was done by Bradford method, while the determination of optimum working conditions and lipase specific activity was performed by titrimetric method. The results showed that total protein concentration in avocado seeds germination was 458 μg / mL. The optimum working conditions on avocado seed sprouts are the degree of acidity (pH) 6, temperature 35 oC, and 1.5% v/v substrate concentration. The lipase specific activity of avocado seeds germination is 144,1 U / mg.